Disability Inclusion in Church Service: Realizing God's Mission of Mercy and Justice - Luosje Treesje Luas (Publikasi Indonesia, 2024)
The Church is called to be a sign, an instrument, and an embodiment of God's love and justice for the world. One of the church's important vocations is to serve the vulnerable and marginalized, including those with disabilities. The Church needs to reflect on God's heart and mission that is full of mercy, equality, and justice for all without exception. This article will explore how the church can live out this divine calling by actively involving congregational members who have disabilities in ecclesiastical life and ministry. So far, church service is still in the concept of charitable diaconia rather than diaconia of community initiative development or also transformative diaconia. The research method used to solve this problem is qualitative. The expected outcome of this study is to ensure the full involvement and participation of everyone with disabilities in church service, as well as an appreciation for their dignity and uniqueness.